Immunopathology of Recurrent Vulvovaginal Infections: New Aspects and Research Directions - Kalia, Namarta; Singh, Jatinder; Kaur, Manpreet (Frontiers in Immunology, 2019)
Recurrent vulvovaginal infections (RVVI), a devastating group of mucosal infection, are severely affecting women’s quality of life. Our understanding of the vaginal defense mechanisms have broadened recently with studies uncovering the inflammatory nature of bacterial vaginosis, inflammatory responses against novel virulence factors, innate Type 17 cells/IL-17 axis, neutrophils mediated killing of pathogens by a novel mechanism and oxidative stress during vaginal infections. However, the pathogens have fine mechanisms to subvert or manipulate the host immune responses, hijack them and use them for their own advantage. The odds of hijacking increases, due to impaired immune responses, the net magnitude of which is the result of numerous genetic variations, present in multiple host genes, detailed in this review. Thus by underlining the role of the host immune responses in disease etiology, modern research has clarified a major hypothesis shift in the pathophilosophy of RVVI. This knowledge can further be used to develop efficient immune-based diagnosis and treatment strategies for this enigmatic disease conditions. As for instance, plasma-derived MBL replacement, adoptive T-cell and antibody-based therapies have been reported to be safe and efficacious in infectious diseases. Therefore, these emerging immune-therapies could possibly be the future therapeutic options for RVVI.